(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the problem of using interactive methods of creative ability in primary education mother tongue and reading lessons, how to increase the effectiveness of the lesson is highlighted. Also, the author comments on the characteristics of using non-traditional methods to focus the student’s attention, develop resourcefulness and creativity. The scientific definitions of the word creativity and the opinions of our Grandfathers are included in this article. Creativity is an imaginative vision; is the ability to evaluate.